Hungary : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that Hungary's economy has emerged from the 2012 recession and posted 1.1 percent growth in 2013, mainly driven by government investment and consumption, and also net exports. Private demand-although strengthening on the back of accommodative monetary conditions and improved market confidence-remained weak, and credit to the retail and corporate sectors continued to contract, albeit at a slowing pace. Hungary's medium-term growth prospects remain subdued, as private consumption is still hampered by the ongoing repair of households' balance sheets; the weak business environment continues to weigh on private investment.